(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Immunological infertility is a multifaceted condition resulting from the production of antisperm antibodies (ASA), which can significantly impair the fertilization process. These antibodies are produced by the immune system of either the male or female partner in response to sperm cells, which are mistakenly recognized as foreign agents. Their impact varies, ranging from direct sperm damage to impaired motility and fertilization potential. Understanding the role of ASA and cytokines in sperm functionality is crucial for developing effective diagnostic and therapeutic approaches. This article provides a comprehensive review of the mechanisms of ASA formation, their impact on sperm structure and function, and the role of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. Additionally, the study explores the correlation between ASA levels and pregnancy outcomes, including the risk of spontaneous miscarriages and preterm births, as well as the effectiveness of various therapeutic strategies in enhancing conception rates in assisted reproductive technologies (ART).